Educação Ambiental: propostas de caminhos para a conservação da biodiversidade - Ferreira, Larissa (2021)
The objectives of the internship were to provide greater learning about the works and actions aimed at the Environmental Education (EA) and enable a more in-depth training in the planning, execution and evaluation of activities, contents and materials to bring the EA theory and its practice closer. In relation to the internship work plan, in particular, the following objectives can be highlighted: ● To plan and monitor virtually the company's environmental education activities; ● To analyze and propose changes in educational materials aimed at conserving biodiversity on a digital platform; ● To incorporate principles of inclusive education and coherent language into the educational actions carried out; ● To hold training meetings with the team.